Taguchi-Based Multi-Objective Optimization of Energy Management Systems for Reduced Electricity Consumption - T Patel, Mohan; J. Rathod, Nikhil (Journal of Neonatal Surgery, 2024)
Modern energy management systems (EMS) must effectively manage electricity demand in order to increase system performance, save operating costs, and improve dependability. The Taguchi design of experiments strategy is used in this study to optimize electricity demand in a methodical manner. In order to maximize system efficiency while minimizing electricity consumption and mean squared deviation (MSD), three control parameters, each at three levels, were examined. The most important parameters and their ideal settings were determined using response tables, analysis of variance (ANOVA), and signal-to-noise (S/N) ratio analysis. The findings show that whereas factor C is primarily responsible for increasing system efficiency, factor B has the greatest influence on electricity demand and MSD, accounting for over 90% of the total variation. While maximum efficiency was attained at A₃B₂C, the ideal parameter combination for reducing electricity demand and MSD was determined to be A₁B₁C₂.₃. With R2 values above 96%, the generated models demonstrate great predictive accuracy